On the non-perturbative realization of QCD gauge-invariance - Fried, H. M.; Grandou, Thierry; Hofmann, Ralf (Modern physics letters, 2017)
A few years ago the use of standard functional manipulations was demonstrated to imply an unexpected property satisfied by the fermionic Green’s functions of QCD: effective locality. This feature of QCD is non-perturbative as it results from a full integration of the gluonic degrees of freedom. In this paper, previous derivations of effective locality are reviewed, corrected, and enhanced. Focusing on the way non-Abelian gauge-invariance is realized in the non-perturbative regime of QCD, the deeper meaning of effective locality is discussed.